THE ANTIBACTERIAL MOUTHWASH OF TAPAK LIMAN LEAVES EXTRACT ( Elephanthopus scaber L ) AGAINST Streptococcus mutans - IFMAILY IFMAILY (Yayasan Pendidikan Medika Indonesia, 2020)
Biodiversity Indonesia has been widely used as a treatment for Indonesian people. One of them is a plant of Tapak liman that efficacious antibacterial. The purpose of this research to know the formulation of the leaf extract of Tapak Liman which can be made as a antiseptic mouthwash and know the inhibiting power test of the leaf extract of the Tapak Liman against Streptococcus mutans. Streptococcus mutans can make the extra-cell polysaccharide consists mainly of a glucose polymer that forms a plaque matrix and can stick on the surface of the tooth causing plaque buildup and bad breath. This research was purely experimental by made the Tapak Liman leaves into a viscous extract, then it was made as the antiseptic mouthwash and testing of its inhibiting power against Streptococcus mutans. The antiseptic mouthwash of leaf extract of Tapak Liman is made into five formulas consist of F0 (base), F1 ( 10% ), F2 ( 20% ), F3 ( 30% ) and Fp as comparator ( Betadin mouthwash ). The antibacterial activity test of the antiseptic mouthwash of Tapak Liman with the diffusion method using the Nutrient Agar media (NA) and data was analyzed by One Way ANOVA. The result of research that the leaf extract of Tapak Liman in 3 concentrations variance can be formulated into the antiseptic mouthwash. The antiseptic mouthwash provides an average diameter – the average resistance of the barrier is F0 (8.40 mm), F1 (12.40 mm), F2 (12.80 mm) and F3 (13.60 mm) and Fp (14.80 mm). Conclusion of research that all of the formula leaf extract of Tapak Liman can be made as the antiseptic mouthwash, and all formulas that give inhibiting power test against the Streptococcus mutans